Wound Healing in Diabetic Patients - Muhammad Bilal, Abdul Hanan, Muhammad Saleem Bashir, Muhammad Shakeel Basit, Muhammad Adeel Abbas (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Diabetes mellitus (DM) is a very common disease that results from the body’s inability to maintain blood glucose level within normal limits. Blood glucose levels are either too high or too low. One study shows that up-to 30% people with DM experience skin problems. If blood sugar levels are well controlled, the rate of wound healing and developing a severe infection is significantly less. Regarding management of wound in diabetic patients, keep wounds dry with meticulous dressing, limb elevation, protect the surgical fixation in splint or braces for an extended period of time and patient education to keep in touch wither consultant and promptly report any unusual discomfort, pain, wound discharge, soaking of dressing and systemic symptoms. Objectives: the objective of this study is to identify the risk of wound infection and rate of healing in diabetic patient. Materials and Methods: The study was conducted at orthopedic department of Gulab Devi hospital. It was a Cross sectional study. The data was collected from September 2021 to February 2022. Non–Probability purposive sampling technique was used. The data was collected from indoor of Gulab Devi Chest Hospital Lahore and informed consent was taken from all the patients. The target populations were those who have diabetes mellitus and treated in orthopedic ward at Gulab Devi hospital Lahore. Diabetic patients enrolled in the presented study n=60. Results: our patient population was 28 to 55 year old with mean age 40years. 83% were in 35 to 40 age group. Wound problems were frequently encountered in patients with uncontrolled diabetes and 50% (n=30) of these patients had at least one wound complication after operation. And 71% (n=43) patients had increased pain and delayed recovery of their surgical wounds. When it comes to the relationship between bone health and diabetes, 63% (n=38) patients had history of previous bone fracture and 61% (n=37) patients had deformity of bone. Due to diabetic neuropathy 68% (n=41) patient were weight bearing on fracture site without concern. And the risk of diabetes include slow wound healing 75%. Practical implication; we aim to raise awareness among treating surgeons and physicians of patients presenting with diabetes and planning to undergo surgical intervention. Meticulous wound care and strict control of blood sugar levels are paramount to successful outcome. Conclusion: Diabetes mellitus is a systemic disease associated with uncontrolled blood sugar levels with systemic manifestations. Our study has proved an association of high wound complication with DM patients. Strict diabetic control as well as extra vigilance and meticulous techniques are needed to prevent complications in this group of patients. Keywords: Diabetes mellitus, infected wound, diabetes complications, wound healing